The quality of early breast cancer diagnosis in urban women by doctors of adult polyclinics - V. A. Kozlov; B. A. Polyakov; D. L. Mushnikov; E. L. Funtikova; D. A. Nedavniy (Исследования и практика в медицине)
In oncology, one of the leading places belongs to breast cancer. This problem is particularly significant in the current situation, when the issue of reproductive health of the female population is acute lyuped in connection with the unfavourable demographic trends in our country. Early diagnosis of precancerous diseases and initial stages of cancer is possible only with active search of patients among practically healthy people. However, despite the availability of breast for examination in adult clinics, malignant tumors of these locations are often found with considerable delay. The most important factor in the success of early diagnosis of oncopathology is the work of primary health care physicians. However, there have been no studies on the quality of early diagnosis of breast cancer in urban women in modern seffings. Purpose of the study. to study the quality of early diagnosis of breast cancer in urban women by doctors of adult polyclinics. Materials and methods. Adult clinics №.1, 2, 3, 4, 5, 6, 7, 8, 11, 12 of Ivanovo have been identified as the basis of the study. The study was conducted in 2018. The program of the study included the use of methods: expert, sociological, mathematical and statistical. Surveillance units: a woman with a malignant breast formation living in the city; case of detected and confirmed malignant breast formation. A retrospective analysis of 600 expert opinions was carried out, the survey method on the questionnaire studied women's satisfaction with premorbid prevention in the adult clinic and the availability of early diagnosis of breast cancer (100 patients). The data were processed using applied computer programs. Results. It has been established that the main causes of late diagnosis of breast cancer in urban women are: untimely treatment of the patient in a medical and preventive institution, deviations from the standard of examination of women for oncopathology, errors in diagnosis, features of the course of the disease (lightning or latent form), non-compliance with continuity in the management of the patient.Conclusion. Analysis of expert opinions on advanced cases of breast cancer showed that the bulk of the defects detected are preventable and are associated with low cancer of doctors and failure to fully and properly perform the standard of examination oncopathology.